IMPLEMENTASI KERJA SAMA UNICEF DAN LP MA’ARIF NU JAWA TENGAH DALAM PROGRAM PENDIDIKAN INKLUSIF DISABILITAS (2018-2020) - ', Rania; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Inclusive education has been recognized as a solution to overcoming gaps in the percentage of children in formal education, both by sons of disability and non-disability. Indonesia realized that to achieve this challenging goal would need to involve stakeholders. The study tries to explain how UNICEF and ma 'arif nu nu are collaborating to reach SDGS no.4, which is a quality education. Both sides work together to overcome challenges, such as discrepancies in data collection, negative stigma, the struggle faced by teachers, and family-related poverty. These efforts are analyzed by comparing them with international, national frameworks, planning of inclusive education sectors, CRPD rights conventions, and RAN PD to understand their effectiveness. The writer uses qualitative descriptive research methodology and data collection obtained from interviews, finals of the Indonesian report of UNICEF, and the books, journals, headlines, and data listed on the official related page. In this study, the theory of international cooperation was used by zartman & touval to explain the co-operation of producing something that could not have been generated on its own. The research found that the cooperation could increase the 5 percent school intervention index between children and disability, so their welfare rate is now at 91 percent of students without disability. Keywords: Inclusive Education, UNICEF, LP Ma’arif NU Central Java